Gambaran Histopatologi Telapak Kaki Depan (metacarpal) pada Anjing yang Terserang Tumor Kulit: GAMBARAN HISTOPATOLOGI - Azhar, Annisha Permata Nurul; Moekti, Bima Satria; Palestin, Palestin (VITEK : Bidang Kedokteran Hewan, 2022)
A 12 year old mixed breed dog came to Clinic K and P Surabaya with complaints of a lump on the left forefoot by the owner. A skin tumor is an uncontrolled growth of cells in the skin and underlying tissue that can be malignant or benign. After a physical examination and surgical removal of the skin tumor on the forefoot. Organ tumors are made preparations. Then the observations were made under a microscope with a magnification of 200x and 400x. Histopathological picture of skin tumors showed cell differentiation such as cell necrosis in the tissue, degenerative changes in the cytoplasm and nucleus and irregular growth and number of cells.